Factors that affect the epistemology of group learning: A research-based analysis. - Victoria Marsick; Elizabeth Kasl (Adult Education Research Conference, 1997)
This examination of factors that affect group learning is a first step toward developing a pedagogy of group learning, in contrast to individual learning.